The Effect of Microsystem Environment Toward the Students’ English Achievement in Pesantren-Based Junior High School - Dzukhriyah, Silfa; Adisti, Aprilian Ria (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
This study aims to examine the effect of the microsystem environment on students’ English achievement in a pesantren-based junior high school setting. The microsystem, as part of Bronfenbrenner’s ecological theory, includes the students’ immediate environments such as family, peers, teachers, and school infrastructure, which are considered crucial in shaping their academic performance. Using a quantitative correlational design, data were collected from 151 junior high school students in two pesantren-based schools through a validated questionnaire and their English exam scores. The analysis was conducted using simple linear regression. The findings reveal that the microsystem environment has a significant and positive effect on students’ English achievement (R² = 0.152, p < 0.01), this indicates that 15.2% of the variation in students’ English achievement is explained by their microsystem environment. The regression coefficient indicates that a more supportive and engaging microsystem is associated with higher English proficiency among students. These findings suggest the need for pesantren-based schools to enhance supportive and engaging environments to optimize students' academic success, particularly in English language learning.